Task view reduction Algorithm based on Rough sets in Gloud Storage - Yiyi Xu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Knowledge reduction is one of the important research issues in rough set theory, which applies knowledge reduction theory to reduction the massive task sets in Gloud storage. At first, an equivalence class evolved from subviews will be obtained after task update, Then, a parallel running strategy is designed for large-scale data , and calculate the optimal attributes based on the task set with minimal time overhead, to this end, delete redundant views according to the optimal attribute sets. Finally, the optimized task combination views are obtained. Simulation results shows it has better overall performance in time span, runtime, speed-up ratio and scalability when compared with the original algorithm that under same conditions, the actual examples used in analysis indicate the effectiveness of this method. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4282